New species and new records of Miroculis Edmunds (Ephemeroptera: Leptophlebiidae) from Southeastern Brazil - Salles, F. F.; Lima, M. M. (Zootaxa, 2011)
In the present work, based mainly on material from environmental protection areas in the State of Espírito Santo, we describe a new species of Miroculis (Miroculis). The male imago of M. (M.) caparaoensis, sp. nov. can be distinguished from other members of the subgenus by the following combination of characteristics: 1) dorsal portion of eyes on a short stalk, dorsal upper portion circular with 12–18 large-sized facets in longest row; 2) forewings with membrane translucid, longitudinal and crossveins brown; 3) abdominal color pattern; 4) posteromedian margin of styliger plate with small concavity; 5) penes length approximately 0.70 length of forceps segment 1. Miroculis (Ommaethus) mourei and M. (M.) fittkaui are reported for the first time from the region.